Kritik Pemahaman HadÃ®th Negara Islam Irak dan Suriah (NIIS) - Arromadloni, Muhammad Najih (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2016)
The politization of á¸¥adÃ®th within social and political dimension has been in fact an undeniable matter since the beginning of the Islamic history. The proponents of Negara Islam Irak dan Suriah (NIIS) [The Islamic State in Iraq and Syria (ISIS)], as a modern political movement, claimá¸¥adÃ®th as one of their main religious, social, and political justifications, which is actually incongruous to the mainstream understanding of the global Muslim community. It is, therefore, a necessity to raise a discourse for analyzing the understanding of NIISâs proponents oná¸¥adÃ®th based on the Method of Critique of Matn or MaâÃ¢nÃ® al-HadÃ®th. The research focuses mainly on Dabiq magazine which is officially issued by the NIIS. It is analyzed descriptively, critically, and comparatively. The research concludes that the understanding of NIISâs proponents oná¸¥adÃ®th on khilÃ¢fah, jihÃ¢d, hijrah, Ã®mÃ¢n and al-malh}amat al-kubrÃ¢ has erroneously deviated from the common and approved methods employed by the scholars ofá¸¥adÃ®th. NIISâs understanding has been widely criticized by the scholars ofá¸¥adÃ®th of being partial, inconsistent, less careful, and has no theological, ideological and political root as well as historical evidences.